Reflex Photosensitive Epilepsy - Arya, Kapil (Journal of Pediatric Epilepsy, 2019)
Reflex seizure provoked by light or pattern stimulation are an interesting and, at times, difficult to treat entity. Such seizures occur in patients with a variety of well-described epileptic syndromes, although in most spontaneous seizures are also described. This paper attempts to describe epileptic syndromes with primarily light or pattern provoked seizures.
Keywords: reflex; photosensitive; pattern sensitive; epilepsy